Process control and development in wire and arc additive manufacturing - Sequeira Almeida, P. M. (Cranfield University, 2012)
This thesis describes advancements in the modelling, optimisation, process control and mechanical performance of novel high deposition rate gas metal arc welding processes for large scale additive manufacturing applications. One of the main objectives of this study was to develop fundamental understanding of the mechanisms involved during processing with particular focus on single layer welds made of carbon steel using both pulsed-current gas metal arc welding and cold metal transfer processes. The effects of interactions between critical welding process variables and weld bead and plate fusion characteristics are studied for single and multi-layers. It was shown that several bead and plate fusion characteristics are strongly affected by the contact tip to work distance, TRIM, wire feed speed, wire feed speed to travel speed ratio, and wire diameter in pulsed-current gas metal arc welding. The arc-length control, dynamic correction and the contact tip to work distance are shown to strongly influence the weld bead geometry in the cold metal transfer process. This fundamental knowledge was essential to ensure the successful development of predictive interaction models capable of determining the weld bead geometry from the welding process parameters. The models were developed using the least-squares analysis and multiple linear regression method. The gas tungsten constricted arc welding process was utilised for the first time for out-of-chamber fabrication of a large scale and high-quality Ti-6Al-4V component. The main focus was, however, in the use of the cold metal transfer process for improving out-of-chamber deposition of Ti-6Al-4V at much higher deposition rates. The effect of the cold metal transfer process on the grain refinement features in the fusion zone of single layer welds under different torch gas shielding conditions was investigated. It was shown that significant grain refinement occurs with increasing helium content. The morphological features and static mechanical performance of the resulting multi-layered Ti-6Al-4V walls were also examined and compared with those in gas tungsten constricted arc welding. The results show that a considerable improvement in static tensile properties is obtained in both testing directions with cold metal transfer over gas tungsten constricted arc welding. It was suggested that this improvement in the mechanical behaviour could be due to the formation of more fine-grained structures,which are therefore more isotropic. The average ultimate tensile strength and yield strength of the as-deposited Ti-6Al-4V material processed via cold metal transfer meet the minima specification values recommended for most Ti-6Al-4V products. Neutron diffraction technique was used to establish the effect of repeated thermo-mechanical cycling on the generation, evolution and distribution of residual stresses during wire and arc additive manufacturing. The results show a significant redistribution of longitudinal residual stresses along both the substrate and multi-bead with repeated deposition. However, a nearly complete relaxation occurs along the built, once the base plate constraint is removed.
Keywords: Additive manufacturing; arc welding; wire and arc additive manufacturing; cold metal transfer; pulsed-current gas metal arc welding; Ti-6Al-4V; weld bead geometry; regression analysis; residual stresses; neutron diffraction